2020
DOI: 10.7717/peerj.9534
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod IGF, relaxin and gonadulin, putative orthologs of Drosophila insulin-like peptides 6, 7 and 8, likely originated from an ancient gene triplication

Abstract: Background Insects have several genes coding for insulin-like peptides and they have been particularly well studied in Drosophila. Some of these hormones function as growth hormones and are produced by the fat body and the brain. These act through a typical insulin receptor tyrosine kinase. Two other Drosophila insulin-like hormones are either known or suspected to act through a G-pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 70 publications
2
87
0
Order By: Relevance
“…In the dilp8 mutant the effects might reflect the loss of action of endogeneous DILP8 on its receptor. However, it is possible that the ectopic DILP8 may act not only on the GPCR Lgr3, but also on the insulin receptor, dInR (a receptor tyrosine kinase), similar to the other Drosophila relaxin-like peptide, DILP7 (53,54). It was actually shown that dInR could be captured by DILP8 in a ligand capture assay, suggesting that DILP8 is able bind to both Lgr3 and dInR (13).…”
Section: Functional Roles Of Dilp8 Signalingmentioning
confidence: 99%
“…In the dilp8 mutant the effects might reflect the loss of action of endogeneous DILP8 on its receptor. However, it is possible that the ectopic DILP8 may act not only on the GPCR Lgr3, but also on the insulin receptor, dInR (a receptor tyrosine kinase), similar to the other Drosophila relaxin-like peptide, DILP7 (53,54). It was actually shown that dInR could be captured by DILP8 in a ligand capture assay, suggesting that DILP8 is able bind to both Lgr3 and dInR (13).…”
Section: Functional Roles Of Dilp8 Signalingmentioning
confidence: 99%
“…Methods employed in bioinformatics have been described in detail in a previous manuscript (Veenstra, 2020). For the expression of SIFamide, SMYamide and their putative receptors in Periplaneta the followoing transcriptome short read archives (SRAs) were analyzed: DRR014884, DRR014885, DRR014886, DRR014887, DRR014888, DRR014889, SRR921630, SRR5286150, SRR5286151, SRR5286152, SRR5286153, SRR5286154, SRR1184457, SRR1184458, SRR1322009, SRR2994649, SRR2994650, SRR3056857, SRR3056858, SRR3089536, SRR3089537, SRR3089538, SRR3289663, SRR3289684, SRR3289687, SRR5097509, SRR5097510, SRR5097511, SRR5097512, SRR5097513, SRR5097514, SRR5097515 and SRR5097516.…”
Section: Methodsmentioning
confidence: 99%
“…Coding sequences for SIFamide and SMYamide precursors as well as those for putative SIFamide receptors were deduced from transcriptome and genome data as described (Veenstra, 2020). All these sequences are listed in the supplementary spreadsheet.…”
Section: Methodsmentioning
confidence: 99%
“…The genomes were downloaded from https://www.ncbi.nlm.nih.gov/genome. For many of these species there are also significant amounts of RNAseq data and these were analyzed using the sratoolkit (https://trace.ncbi.nlm.nih.gov/Traces/sra/sra.cgi?view=software ) in combination with Trinity (Grabherr et al, 2011) using methods described in detail elsewhere (Veenstra, 2020b). Some protein sequences were found in the NCBI database, but several of them contain errors or are incomplete.…”
Section: Sequence Analysismentioning
confidence: 99%
“…This raises the interesting question as how this apparent jump from one type of receptor to another may have come about. In cockroaches, termites and stick insects three different irp genes, gonadulin, arthropod insulin-like growth factor (aIGF) and arthropod relaxin, are located next to one another in the genome and thus likely originated from a local gene triplication (Veenstra, 2020b). To avoid confusion with the vertebrate relaxins and related peptides, the arthropod relaxins will be referred to as Drosophila ilp7 (dilp7) in this manuscript.…”
Section: Introductionmentioning
confidence: 99%